A web experience exploring spatio–linguistic data: the case of place-making signs in Northern Sweden - Coppélie Cocq; O. Cenk Demiroglu; Urban Lindgren; Lena Granstedt; Eva Lindgren (Journal of Maps)
Previous research has highlighted the limitations encountered in representing the dynamism of language use and contacts. Here, linguistic landscapes from five towns in Northern Sweden are the point of departure for investigating novel perspectives through the geovisualization of multilingualism, with the ultimate aim of understanding how languages in our surroundings help construct public spaces. As an outcome, a web GIS application, based on 6865 thematically analyzed photographs, was developed as an interactive resource for visualizing and sharing the data and enabling new modes of analysis and new research questions. The article describes the data collection and curation processes, app development using GIS software and software-as-a-service, the eventual app design and interaction, and the update and maintenance plans, as well as discussing challenges and considerations related to temporalities, spatialities, and technicalities. The web GIS has potential applications in spatial analysis, research communication, and education.